Insulin Resistance with Associated Hyperinsulinemia as a Cause of the Development and Worsening of Heart Failure - Umberto Attanasio; Valentina Mercurio; Serafino Fazio (Biomedicines)
Despite the considerable progress that has been made with regard to the prevention and treatment of cardiovascular diseases, heart failure (HF) remains a particularly important cause of recurring hospitalizations, with relevant social and healthcare costs, and it is a significant cause of mortality; as such, there is a need for continuous efforts to improve our understanding of its complex pathophysiology and refine relevant therapeutic strategies [...]